Ionopsis × atalibae (Orchidaceae, Oncidiinae), a new natural hybrid from the Brazilian Amazon - Krahl, Amauri Herbert; Krahl, Dayse Raiane Passos; Pansarin, Emerson Ricardo (Phytotaxa, 2021)
Hybridization plays a relevant role in the evolution and diversification of flowering plants. Natural hybridization has been commonly recorded in some orchid groups. During fieldwork in a Citrus plantation in the Brazilian Amazon, plants of Ionopsis utricularioides, I. satyrioides and an unidentified taxon with intermediate morphology between both sympatric species were found. The plants with intermediate features are most likely a natural hybrid between I. utricularioides and I. satyrioides described here as I. × atalibae.